Research-led curriculum development: pilot study on Mathematics - Kalam, Md. Abul; Ashrafuzzaman, SK. Md.; Bareque, Md Abdul; Imam, Syeda Rumnaz (BRAC Research and Evaluation Division (RED), 2020)
The EDU of BRAC's education program has made changes in its curriculum based on the monitoring, research and internal Survey reports which suggested that learners faced difficulty with many sections of different subject areas. The new curriculum covers the competencies specified by the NCTB, and gives focus on making books more activity based and providing separate workbooks and teachers' guides. This pilot study attempted to develop an assessment methodology for assessing what learners know, can do and understand in terms of expected learning outcome as well as the appropriateness of content, context and methodology for achieving expected learning outcome, in order to evaluate the curriculum towards research-led curriculum development with special reference to problem solving in Mathematics of grade 4. This study being part 1 of two studies is a joint study of RED and EDU.